Transcriptome-metabolome analysis reveals how sires affect meat quality in hybrid sheep populations - Chen, Bowen; Yue, Yaojing; Li, Jianye; Liu, Jianbin; Yuan, Chao; Guo, Tingting; Zhang, Dan; Yang, Bohui; Lu, Zengkui (Frontiers in Nutrition, 2022)
Crossbreeding improves and enhances meat quality and is widely used in sheep production; however, the molecular mechanisms underlying the meat quality of various crossbred sheep remain unknown. In this study, male Southdown, Suffolk and Hu sheep were crossbred with female Hu sheep, and the transcriptomes and metabolomes of the longissimus dorsi muscle of the F1 generation were sequenced to explore how different sire breeds affect meat quality. The results showed that 631 differentially expressed genes and 119 significantly altered metabolites contributed to muscle development characteristics and meat quality-related diversity (P<0.05). These genes and metabolites were significantly enriched in lipid metabolism pathways, including arachidonic acid metabolism and PPAR signaling. Several candidate genes were associated with muscle growth, such as MYLK3, MYL10, FIGN, MYH8, MYOM3, LMCD1, and FLRT1. Among these, MYH8 and MYL10 participated in regulating muscle growth and development and were correlated with meat quality-related fatty acid levels (|r| > 0.5 and p < 0.05). We selected mRNA from four of these genes to verify the accuracy of the sequencing data via qRT-PCR. Our findings provide further insight into the key genes and metabolites involved in muscle growth and meat quality in hybrid sheep populations.